On doctoral (in)visibility and reframing the doctorate for the twenty-first century. Issue 4 (2nd October 2022) - Deem, Rosemary
ABSTRACT: The paper explores how doctoral education and doctoral researchers in Europe are currently positioned, in relation to changes in the conditions of academic work and in the context of recent critiques of the doctorate (Cardoso, S., O. Tavares, C. Sin, and T. Carvalho. 2020. Structural and Institutional Transformations in Doctoral Education: Social, Political and Student Expectations . Palgrave Macmillan/Springer Nature; Whittington, K., and S. Barnes. 2021. "The Changing Face of Doctoral Education." In The Future of Doctoral Education, edited by R. Bongaart, and A. Lee, 5–17. Routledge.). Two research questions, one about doctoral researcher visibility/invisibility and the other concerning how holistic changes to doctoral education might be approached, are posed. The paper first considers the extent to which doctoral researchers are rendered invisible in their universities and what the negative and positive consequences of this are for doctoral candidates. A conceptual framework for examining invisible paid or unpaid work, drawing on Hatton's (Hatton, E. 2017. "Mechanisms of Invisibility: Rethinking the Concept of Invisible Work." Work, Employment and Society 31 (2): 336–351) research about invisible paid work and disadvantage, is used to shape this discussion. The same framework is used to explore both existing critiques of the doctorate and recent significant changes to academic work and how they may have shaped or should shape, doctoral education. Finally, the paper examines a possible holistic reframing of the doctorate, drawing on work by Morley (Morley, L. 2013. Women and Higher Education Leadership: Absences and Aspirations), exploring how doctoral candidates and supervisors as people, universities as organisations and the knowledge that feeds into doctoral theses, could all be changed for the better.